Insights and progress on postoperative analgesia of radical gastrectomy for gastric cancer: a comprehensive review - Linghui Li; Yuanyuan Zhao; Huan Chen; Jianqin Zhao; Mengjun Dai; Qi Wang; Jie Lv; Wei Wang (Frontiers in Pain Research)
Gastric cancer is a common and highly lethal malignancy of the digestive system, with surgical resection as the primary treatment approach. However, postoperative analgesia management remains a major clinical challenge. Postoperative pain not only affects recovery speed but may also lead to complications, thereby influencing prognosis. Recent research on postoperative pain following gastric cancer surgery has expanded, exploring various analgesic methods, including pharmacological therapy, neuraxial blocks, and non-pharmacological approaches, with growing emphasis on individualized analgesia protocols. Despite the proposal of multiple analgesic techniques, current research indicates that their effectiveness and safety are still inadequately assessed in clinical applications. This review aims to discuss the physiological mechanisms of postoperative pain following gastric cancer surgery, modern analgesic strategies, and related research, to provide a theoretical basis and clinical guidance for improving postoperative quality of life.